Reduction of noise using multiple expansion chambers - Hawwa, Muhammad A.; Horoub, MA’Mon M. (Canadian Acoustics, 2011)
Expansion chambers are often used to reduce the noise in different systems like air conditioning systems, exhaust systems, and car muffler systems. This study focuses on the effectiveness of multiple expansion chambers in reducing noise in such systems. Optimized designs are realized by utilizing changes in cross sectional areas, changes in the lengths of the expansion chambers, or combined changes of both. It is found beneficial to apply taper functions to the expansion chambers’ geometry, resulting in similar effects of the window functions utilized in the field of digital signal processing.